Long-Term Relations Among Prosocial-Media Use, Empathy, and Prosocial Behavior. (February 2014) - Prot, Sara; Gentile, Douglas A.; Anderson, Craig A.; Suzuki, Kanae; Swing, Edward; Lim, Kam Ming; Horiuchi, Yukiko; Jelic, Margareta; Krahé, Barbara; Liuqing, Wei; Liau, Albert K.; Khoo, Angeline; et al.
Despite recent growth of research on the effects of prosocial media, processes underlying these effects are not well understood. Two studies explored theoretically relevant mediators and moderators of the effects of prosocial media on helping. Study 1 examined associations among prosocial- and violent-media use, empathy, and helping in samples from seven countries. Prosocial-media use was positively associated with helping. This effect was mediated by empathy and was similar across cultures. Study 2 explored longitudinal relations among prosocial-video-game use, violent-video-game use, empathy, and helping in a large sample of Singaporean children and adolescents measured three times across 2 years. Path analyses showed significant longitudinal effects of prosocial- and violent-video-game use on prosocial behavior through empathy. Latent-growth-curve modeling for the 2-year period revealed that change in video-game use significantly affected change in helping, and that this relationship was mediated by change in empathy.